PAG-IBIG ; Chirstmas [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1988)
The fund that provides opportunities for people to own their lots meets with success when a squatter colony pulls its resources own a piece of property. A look at Christmas homes, i.e., Gigi Carlos who decorated her home for six month.
PAG-IBIG (13 min.) -- Christmas (16 min.)
VHS.
Keywords: PAG-IBIG Fund; Housing -- Finance. -- Philippines; Christmas decorations; Businessmen -- Interviews. -- Philippines